Improving customer satisfaction in proactive service design - Annette Wenninger; Daniel Rau; Maximilian Röglinger (Electronic Markets, 2022)
As an emergent variant of digital and smart services, proactive services (PAS) do not wait for customers to make the first move, but proactively participate in customers' lives and make decisions on their behalf. Due to their novelty, the literature on PAS is in its infancy. Specifically, there is a lack of guidance on designing PAS to meet customer needs. Hence, we examined how customers assess specific features of PAS and whether their assessments differ according to personality traits. To this end, we conducted an online survey via the crowdsourcing platform Prolific, which yielded 259 valid responses. We used a methodological combination of the Kano model, self-stated importance method, and the Five Factor model. Our results reveal that, at the moment, customers do not value features of PAS related to autonomy and that customers engage in paradoxical behavior when assessing the use of personal data. These results allow for a more precise classification and prioritization of the features of PAS tuned to a customer's most prevalent personality trait.
Keywords: M30; O30; L80; L86; 620; Customer satisfaction; Kano model; Proactive services; Personality traits; Service design